Aquatic risk assessment of priority and other river basin specific pesticides in surface waters of Mediterranean river basins. (September 2015) - Silva, Emília; Daam, Michiel A.; Cerejeira, Maria José
Highlights: 29 pesticide compounds analysed in Mediterranean river basins. Derivation of EQSs for 20 pesticide compounds. 13 pesticide compounds pose risk in Portuguese surface waters. Improved classification of ecological status of surface water bodies. Abstract: To meet good chemical and ecological status, Member States are required to monitor priority substances and chemicals identified as substances of concern at European Union and local/river-basin/national level, respectively, in surface water bodies, and to report exceedances of the environmental quality standards (EQSs). Therefore, standards have to be set at national level for river basin specific pollutants. Pesticides used in dominant crops of several agricultural areas within the catchment of Mediterranean river basins ('Mondego', 'Sado' and 'Tejo', Portugal) were selected for monitoring, in addition to the pesticides included in priority lists defined in Europe. From the 29 pesticides and metabolites selected for the study, 20 were detected in surface waters of the river basins, seven of which were priority substances: alachlor, atrazine, chlorfenvinphos, chlorpyrifos, endosulfan, simazine and terbutryn, all of which exceeded their respective EQS values. QSs for other specific pollutants were calculated using different extrapolation techniques (i.e. deterministic or probabilistic) largely based on the method described in view of the Water Framework Directive. Non-acceptable aquatic risks were revealed for molinate, oxadiazon, pendimethalin, propanil, terbuthylazine, and the metabolite desethylatrazine. Implications of these findings for the classification of the ecological status of surface water bodies in Portugal and at the European level are discussed.